Mangrove development and carbon storage on an isolated coral atoll. (25th June 2020) - Yamano, Hiroya; Inoue, Tomomi; Baba, Shigeyuki
Abstract: This study investigates the functions and vulnerability of mangroves in isolated atoll settings, by showing the mangrove development and carbon storage, based on the radiocarbon ages and detrital organic-carbon contents of cores collected on Fongafale Islet, Funafuti Atoll, Tuvalu. The mangrove peat formed a thin veneer, several tens of centimeters thick, and mangrove development was constrained by the formation of the reef flat. The initial mangrove development (389 cal yr BP) was much more recent than on other islands, possibly because the island is remote and weakly connected to other source islands. However, the mangrove forests in Tuvalu have geomorphic developmental rates and carbon burial rates similar to those in other settings. The mean carbon sequestration rate is six times that calculated previously from land use, land-use change, and forestry (LULUCF) data for Tuvalu. High vulnerability of the mangroves is suggested by the small sediment thickness and recent development of the mangrove forests, as well as by the past vertical accumulation rates potentially smaller than those of future sea-levels rise. The conservation and restoration of mangrove forests should be one of the key issues in sustaining low-lying atoll countries under climate change and increasing anthropogenic pressures.